2001
DOI: 10.1074/jbc.m008501200
|View full text |Cite
|
Sign up to set email alerts
|

Adrenodoxin Reductase-Adrenodoxin Complex Structure Suggests Electron Transfer Path in Steroid Biosynthesis

Abstract: The steroid hydroxylating system of adrenal cortex mitochondria consists of the membrane-attached NADPH-dependent adrenodoxin reductase (AR), the soluble one-electron transport protein adrenodoxin (Adx), and a membrane-integrated cytochrome P450 of the CYP11 family. In the 2.3-Å resolution crystal structure of the Adx⅐AR complex, 580 In mitochondria of the adrenal cortex, the cytochrome P450 enzymes of the CYP11 family catalyze the side chain cleavage of cholesterol to form pregnenolone (P450scc, 1 CYP11A1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
122
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 31 publications
7
122
0
Order By: Relevance
“…To understand the mode of protein-protein interactions in the AdR-Adx-CYP11A1 system, we compared the CYP11A1-Adx complex with the AdR-Adx complex (37). Adx residues involved in the interaction interface with AdR and CYP11A1 greatly overlap (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mode of protein-protein interactions in the AdR-Adx-CYP11A1 system, we compared the CYP11A1-Adx complex with the AdR-Adx complex (37). Adx residues involved in the interaction interface with AdR and CYP11A1 greatly overlap (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FR, a 50-kD mitochondrial flavoprotein, participates in the cleavage of cholesterol side chain to form pregnenolone, cortisol, and aldosterone in a multi-step biosynthesis, which generates molecular oxygen by reductive splitting of dioxygen and requires the transfer of electrons by FR via ferredoxin to cytochrome P450 (Muller et al, 2001). Here, we and Hwang et al (2001) have found that in addition to the biosynthesis of steroid hormones, FR sensitizes cancer cells to ROSinduced apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…An in-depth understanding of these reactions requires knowledge of the role of protein dynamics in complex assembly and the geometries of the complex that are compatible with interprotein electron transfer (eT). 1 A role for interdomain flexibility has been demonstrated in eT both within a single molecule (3)(4)(5) and between molecules (6).…”
mentioning
confidence: 99%